J-Shaped Relationship Between Serum Prolactin and Metabolic-Associated Fatty Liver Disease in Female Patients With Type 2 Diabetes - Zhu, Cuiling; Ma, Huihui; Huang, Dongdong; Li, Guifang; Gao, Jingyang; Cai, Meili; You, Hui; Bu, Le; Qu, Shen (Frontiers in Endocrinology, 2022)
Background: Metabolic associated fatty liver disease (MAFLD) has become a worldwide epidemic. Prolactin (PRL), a pituitary hormone, has been linked to MAFLD. As a result, we set out to look into the relationship between serum PRL and the risk of MAFLD in patients with type 2 diabetes (T2DM). Methods: A total of 724 adults with T2DM were enrolled and categorized as MAFLD and Non-MAFLD groups. Anthropometric data, biochemical parameters, and serum PRL levels were collected. Liver steatosis and fibrosis were assessed using FibroScan. Patients were stratified into normal PRL (NP) and high PRL (HP) groups and divided into four groups based on serum PRL quartiles. Multivariate logistic regression analysis was performed to evaluate the association between serum PRL and MAFLD risk. Results: Female but not male patients with MAFLD, liver steatosis, and fibrosis had significantly lower PRL levels in the NP group but higher PRL levels in the HP group than their counterparts. The proportions of MAFLD, liver steatosis, and fibrosis were significantly decreased in the NP group but increased in the HP group across the PRL quartiles in females but not males. After multivariate adjustment, the adjusted ORs (AORs) and 95%CI for MAFLD among females was 18.165(3.425-96.336), 1.784(0.658-5.002), 1.744(0.608-4.832), and 1.00(reference) in the NP group (Q1-Q4, P-trend < 0.001), whereas 1.00 (reference), 11.098(1.819-110.356), 15.225(1.996-116.112), and 18.211(2.579-128.568) in the HP group (Q1-Q4, P-trend = 0.020). Such associations were also found between serum PRL and liver fibrosis in females but not males. Conclusion: We observed a J-shaped association between serum PRL and the risk of MAFLD and liver fibrosis in females but not males with T2DM, indicating that PRL may be relevant to MAFLD and its progression in a gender-specific manner.